Report on professional internship with Design Bridge Asia Pte Ltd. - Ng, Siew Hoon. (2008)
This report will provide an in-depth insight into my internship experience at Design Bridge Asia and it will begin with a brief introduction of the company and its business and my job scope as a Client Service intern to enhance understanding of the subsequent content.